WHAT DO YOU SEE HERE FROM THIS PICTURE?: QUESTIONING STRATEGIES OF MASTER TEACHERS IN INDONESIAN VOCATIONAL ENGLISH CLASSROOMS - Rido, Akhyar (TEFLIN Journal, 2017)
This study is an attempt to provide an in-depth understanding of the teaching practices of Indonesian vocational English master teachers, focusing on their use of questioning strategies. Using a qualitative approach, this study was carried out in three vocational schools and involved three selected master teachers. Data were collected through 23 sessions of observations, 40 hours of video-recording, and interviews with 33 students. The findings showed that the master teachers employed an interactive style of teaching and not the monologue norm, where the teachers ask while the students answer the questions. They used close-display, open-referential, and follow-up questions. They also nominated specific students to answer questions, asked questions to the entire class, and repeated questions when there was no response. These strategies made the teachers control the lessons, guide the students towards a particular response, and promote interactions. The students were receptive to the strategies as they were keen to contribute when they were given questions and opportunities to speak. The results of this study can be used by various stakeholders to improve classroom interaction and promote interactive learning.